(untitled) (Research, Society and Development, 2021)
This clinical case reports surgical treatment in an elderly toothless patient after trauma to the lower third of the face. The patient attended the emergency at the Hospital de Fraturas, Recife - PE, complaining of pain in the face after falling from her own height. Radiographic examination revealed bilateral mandibular fracture. Treatment planning was carried out taking into account some important factors for therapeutic success, such as the use of medications, the presence of chronic diseases and physiological and anatomical changes. After diagnosis and correct planning, bone stumps were fixed with two 2.0 system mini-plates. The patient evolved well, without complaints, without paresthesia or paralysis, and the postoperative radiography demonstrated a good reduction in fractures. Thus, it is concluded that the treatment of trauma in elderly patients can be through conservative methods or more complex and invasive techniques, always taking into account the patient’s particular case, aiming at their specific needs and implications.